Effect of the vibration board on the strenght of ankle dorsal and plantar flexor muscles: a preliminary randomized controlled study - Costantino, C.; Pogliacomi, F.; Soncini, G. (Acta Biomedica Atenei Parmensis, 2006)
Aim of this preliminary work is to study the effects of the vibration board on the strength of dorsal and plantar flexor muscles of the ankle through a randomized and controlled observation. Sixteen sedentary right-handed females, ranged from 20 to 30 years of age, were selected; they were not affected by previous ankle sprains and were divided into two randomized groups. The study group followed a vibration board training in the orthostatic position with a 60° flexion of the knee in order to direct its mechanical impulses to the inferior limbs. Each patient of the study group performed daily, for 2 weeks, 10 repetitions that lasted 1 minute each (25 hertz of frequency). The control group followed a training protocol including 10 daily sessions for 2 weeks. Each session included 3 series of 10 repetitions of flexi-extension of the foot versus an opposite resistance of an elastic band, 60 centimetres long, that was stretched till 100 cm. Both groups were tested before and after these training programmes by Biodex isokinetic dynamometer in order to quantify the strength of the plantar and dorsal flexor muscles of the dominant ankle. Peak torque, power and total work of the dorsal and plantar flexor muscles were assessed. A power test at an angular velocity of 60°/sec for five repetitions and a resistance test at an angular velocity of 180°/sec. for 20 repetitions were performed. After the final isokinetic test, the results were submitted to a statistic evaluation (T test of Student) in order to analyze any possible significant differences (p < 0,05) among the initial and final values before and after the treatment. The results of the study group compared to the control group showed a significant increase in the power of the dorsal flexor muscles at an angular velocity of 60°/sec and in the peak torque, power and total work of the plantar flexor muscles at an angular velocity of 60°/sec and 180°/sec.We conclude that the use of the vibration board causes a continuous proprioceptive stimulation which increases neuromuscular receptivity determining a prevailing reinforcement of the plantar flexor muscles of the ankle.